Influence of Personality Type and Sex on Mental Health: An Analytical Study among College Students during Period of COVID-19 - Shinde, Arun Chandu (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
The present study endeavoring to find out the effect of personality and sex on mental health of college students during the COVID-19 Pandemic. Mental Health was assessed of 200 college students (100 boys; 100 girls) by using mental health Scale prepared by Dr. Anand Kumar and Dr. Giridhar Thakur. Age range of students is between 18-23 yrs. To analyze the obtained data two-way ANOVA was used. Results revealed that, Personality has an influence on Mental Health, students having Type-A personality has superior Mental Health comparing to those students who having Type-B personality. There is no sex difference in respect to Mental Health. There is no interaction effect of personality and sex found on mental health.
Keywords: Optimistic attitude; Academic resilience